(untitled) (Encuentros, 2016)
This paper raises on the profession of journalist and strategies for teaching in social communication programs. As a research result, the premise is that every day seems more inevitable than the print media are doomed to extinction. This pushes the authors, first, to shed light on what are the mechanisms for traditional media can survive; and second, to question the needs of a student passionate about the narrative of the press to stand in the field. Article begins with a claudication of objectivity as a paradigm of journalism. He proposes an ethical shift to the subjective, based on the interpretation and humanization of the stories that interest the reader. It also reflects on the application in the educational field and seeks to validate the orientation of teaching and learning to the various journalistic genres. These questions will try to answer in the following lines based on the teaching practice in the program of Social Communication - Journalism at the Universidad Autonoma del Caribe, which has the objective, rather than teach journalism, generate in students skills in quality journalism, and in line with the new realities and narrative techniques.